Pilot testing for feasibility in the study of influence of English movies towards ESL learners’ speaking confidence at tertiary level - Nurul Hidayah Awang Asim; Wardatul Akmam Din; Kamsilawati Kamlun; Suyansah Swanto (Global Academic Excellence (M) Sdn Bhd, 2022)
In order to evaluate the methods for participant recruitment, the usability of the survey questionnaire, and the data collection processes, a pilot test was carried out prior to conducting a study on the impact of English-language films on ESL learners' speaking confidence in tertiary level education. The study's frameworks were adapted from Imitation Theory and Comprehensible Input Theory in order to categorise and list different elements that affected students' speaking confidence. Before beginning the main research study on the impact of English movies, the authors described the pilot testing procedures and feasibility issues explored, as well as the improvements made to the instrument and methodology, in an effort to add to the body of research in this area and to strengthen teaching methods.